Patient-centred IVF : bioethics and care in a Dutch clinic - Gerrits, Trudie (Fertility, reproduction, and sexuality, 2016)
Contemporary Dutch policy and legislation facilitate the use of high quality, accessible and affordable assisted reproductive technologies (ARTs) to all citizens in need of them, while at the same time setting some strict boundaries on their use in daily clinical practices. Through the ethnographic study of a single clinic in this national context, Patient-Centred IVF examines how this particular form of medicine, aiming to empower its patients, co-shapes the experiences, views and decisions of those using these technologies. Gerrits contends that to understand the use of reproductive technologies in practice and the complexity of processes of medicalization, we need to go beyond 'easy assumptions' about the hegemony of biomedicine and the expected impact of patient-centredness.